The exon-skipping oligonucleotide, KitStop, depletes tissue-resident mast cells in vivo to ameliorate anaphylaxis - Barry A. Hedgespeth; Barry A. Hedgespeth; Barry A. Hedgespeth; Barry A. Hedgespeth; Douglas B. Snider; Douglas B. Snider; Douglas B. Snider; Douglas B. Snider; Katie J. Bitting; Glenn Cruse; Glenn Cruse (Frontiers in Immunology, 2023)
IntroductionAnaphylaxis represents the most extreme and life-threatening form of allergic disease and is considered a medical emergency requiring immediate intervention. Additionally, some people with mastocytosis experience recurrent episodes of anaphylaxis during normal daily activities without exposure to known triggers. While acute therapy consists primarily of epinephrine and supportive care, chronic therapy relies mostly on desensitization and immunotherapy against the offending allergen, which is a time-consuming and sometimes unsuccessful process. These treatments also necessitate identification of the triggering allergen which is not always possible, and thus highlighting a need for alternative treatments for mast cell-mediated diseases.MethodsThe exon-skipping oligonucleotide KitStop was administered to mice intradermally, intraperitoneally, or systemically at a dose of 12.5 mg/kg. Local mast cell numbers were enumerated via peritoneal lavage or skin histology, and passive systemic anaphylaxis was induced to evaluate KitStop’s global systemic effect. A complete blood count and biochemistry panel were performed to assess the risk of acute toxicity following KitStop administration.ResultsHere, we report the use of an exon-skipping oligonucleotide, which we have previously termed KitStop, to safely reduce the severity and duration of the anaphylactic response via mast cell depopulation in tissues. KitStop administration results in the integration of a premature stop codon within the mRNA transcript of the KIT receptor—a receptor tyrosine kinase found primarily on mast cells and whose gain-of-function mutation can lead to systemic mastocytosis. Following either local or systemic KitStop treatment, mice had significantly reduced mast cell numbers in the skin and peritoneum. In addition, KitStop-treated mice experienced a significantly diminished anaphylactic response using a model of passive systemic anaphylaxis when compared with control mice.DiscussionKitStop treatment results in a significant reduction in systemic mast cell responses, thus offering the potential to serve as a powerful additional treatment modality for patients that suffer from anaphylaxis.